Endogenous Versus Exogenous Rules in Water Management: An Experimental Cross-country Comparison. Issue 4 (2nd October 2017) - Ibele, Benedikt; Sandri, Serena; Zikos, Dimitrios
Abstract: This paper draws on institutional and experimental economics to investigate the role of exogenous and endogenous rules in irrigation systems. The hypotheses we examine argue that despite the differences between socio-economic and political settings, (1) endogenous rule-crafting can help water users to overcome appropriation and provision dilemmas in water-scarce environments like in the East Mediterranean countries and that (2) in market-like water governance systems, institutions other than the market itself, are less influential for overcoming appropriation and provision dilemmas than in hybrid governance systems. These hypotheses are being tested comparing the results of field experiments conducted in Jordan, the Republic of Cyprus and North Cyprus with 70 farmers. Field experiments simulate asymmetric access to resources and are based on variations of the irrigation game by Cardenas et al. to model and test asymmetric distribution of investment, harvest and revenue that favours upstream users. Empirical evidence shows that externally imposed allocation rules are able to bring in more equal distribution of revenue among upstream–downstream users but is likely to reduce the volume of investment and revenue, without resolving issues of free-riding. The authors argue that given the opportunity, water users (small farmers in our experiments) are able to craft their own rules improving the overall performance of the group in terms of investment and revenue, with a parallel improvement of equity in distribution. The implications and policy relevance of such findings are briefly discussed as they contradict typical practices of top-down policy delivery in the selected cases.